Left Behind Voters, Anti-Elitism and Popular Will - Benoit Crutzen; Dana Sisak; Otto Swank (Tinbergen Institute, 2020)
Two common characteristics of populism are anti-elitism and favoring popular will over expertise. The recent successes of populists are often attributed to the common people, the majority of voters, being left behind by mainstream parties. This paper shows that the two characteristics of populism are responses to the common people being left behind. We develop a model that highlights two forces behind electoral success: numbers and knowledge. Numbers give the common people an electoral advantage, knowledge the elite. We show that electoral competition may lead parties to cater to the elites interest, creating a left-behind majority. Next, we identify conditions under which a left-behind majority encourages entry by a party offering an anti-elite platform. Finally, we identify conditions under which parties follow the opinion of the common people when that group would benefit from parties relying on experts.
Keywords: D72; D83; 330; Electoral competition; Populism; Pandering; Information